11x-2(x-7)=9(x+1)+9

Simple and best practice solution for 11x-2(x-7)=9(x+1)+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11x-2(x-7)=9(x+1)+9 equation:



11x-2(x-7)=9(x+1)+9
We move all terms to the left:
11x-2(x-7)-(9(x+1)+9)=0
We multiply parentheses
11x-2x-(9(x+1)+9)+14=0
We calculate terms in parentheses: -(9(x+1)+9), so:
9(x+1)+9
We multiply parentheses
9x+9+9
We add all the numbers together, and all the variables
9x+18
Back to the equation:
-(9x+18)
We add all the numbers together, and all the variables
9x-(9x+18)+14=0
We get rid of parentheses
9x-9x-18+14=0
We add all the numbers together, and all the variables
-4!=0
There is no solution for this equation

See similar equations:

| 23x-1=24x+36 | | 30x+x+25*20=3750 | | 3(x-5)+2x=5(x+4)-35 | | 5+2(3x-6)=9-4(2x+1) | | 8x+3=3(3x-10) | | 10x^2+18x−88=0 | | 2/4a=-2 | | 10x​2​​+18x−88=0 | | 0.5(x+100)=0.57x-482 | | (x-3)-10=9 | | 0.2(3-3x)+0.2x=4.2 | | 3x+5x+25,x=3 | | 10=7+x/3 | | (x-3)8=14 | | 0.3(2z+5)+2.9=0.4(2z-4) | | 3x+5x+25=3 | | 4(x-2)-5(2x-6)=8(x+1)-3(2+3) | | 13+9x=10.5-1 | | -0.2(x-7.5)=8.9 | | 9x=-3.5 | | 16y=12^2 | | a-(-5-2a)=7(a-1)-2 | | 6x/15=5 | | .32x=2.1x+8.8 | | 6x/15+15=20 | | 2y/7*7/8=13/56 | | 2.7=21.2-x | | y+0.4^-2=6 | | 8x+13=9x+1 | | 8a-8=8a+8 | | 7(10-x=126 | | 25(x-8)^2=81 |

Equations solver categories